Late outcome analysis of the Braile Biomédica® pericardial valve in the aortic position - Lisandro Gonçalves Azeredo; Elinthon Tavares Veronese; José Augusto Duncan Santiago; Carlos Manuel de Almeida Brandão; Pablo Maria Alberto Pomerantzeff; Fabio Biscegli Jatene (Brazilian Journal of Cardiovascular Surgery, 2014)
Objective: Aortic valve replacement with Braile bovine pericardial prosthesis has been routinely done at the Heart Institute of the Universidade de São Paulo Medical School since 2006. The objective of this study is to analyze the results of Braile Biomédica® aortic bioprosthesis in patients with aortic valve disease. Methods: We retrospectively evaluated 196 patients with aortic valve disease submitted to aortic valve replacement with Braile Biomédica® bovine pericardial prosthesis, between 2006 and 2010. Mean age was 59.41±16.34 years and 67.3% were male. Before surgery, 73.4% of patients were in NYHA functional class III or IV. Results: Hospital mortality was 8.16% (16 patients). Linearized rates of mortality, endocarditis, reintervention, and structural dysfunction were 1.065%, 0.91%, 0.68% and 0.075% patients/year, respectively. Actuarial survival was 90.59±2.56% in 88 months. Freedom from reintervention, endocarditis and structural dysfunction was respectively 91.38±2.79%, 89.84±2.92% and 98.57±0.72% in 88 months. Conclusion: The Braile Biomédica® pericardial aortic valve prosthesis demonstrated actuarial survival and durability similar to that described in the literature, but further follow up is required to assess the incidence of prosthetic valve endocarditis and structural dysfunction in the future.